Fast particle behaviour in the Globus-M spherical tokamak. (April 2015) - Bakharev, N.N.; Chernyshev, F.V.; Goncharov, P.R.; Gusev, V.K.; Iblyaminova, A.D.; Kornev, V.A.; Kurskiev, G.S.; Melnik, A.D.; Minaev, V.B.; Mironov, M.I.; Patrov, M.I.; Petrov, Yu.V.; et al.
Abstract The behaviour of the fast particle population during 18 keV hydrogen and 26 keV deuterium neutral beam injection in deuterium plasmas is investigated. Experiments reveal large fast ion losses. The experimental results are confirmed using different types of modelling: simulation using the NUBEAM module, solution of the Boltzmann kinetic equation and solution of the 3D fast ion tracking algorithm. The dynamics of the energetic particle redistribution and losses during sawtooth oscillation and toroidal Alfvén eigenmodes are studied. A method to decrease fast ion losses under the current conditions (0.4 T, 0.2 MA) is shown. The influence of the plasma parameters on the energetic ion confinement rate is investigated. Modelling for the Globus-M2 conditions (1 T, 0.5 MA) is performed.